The art of manufacturing : overcome control challenges for increasing efficiency in manufacturing using real-world examples /: overcome control challenges for increasing efficiency in manufacturing using real-world examples. (2023) - Deshpande, Ninad; Pothukuchi, Sivaram
No abstract available